Nest and nest characteristics of common kingfisher (Alcedo atthis) and white-throated kingfisher (Halcyon smyrnensis) in Bangladesh (Bangladesh Journal of Zoology, 2016)
This study was on nest and its site, measurement and building time of Common Kingfisher (Alcedo atthis) and White-throated Kingfisher (Halcyon smyrnensis) in Bangladesh. After pair formation, both species chose nearly 900 sloppy sandy-loam areas for nesting. The nests were tunnel-like, the length of which were 31 to 48 cm (median 36.5 cm, n = 8) for Common Kingfisher and 44 to 86 cm (median 59.25 cm, n = 10) for White-throated Kingfisher. The horizontal diameter of the outer opening of the hole of White-throated Kingfisher was almost double (6.5 to 14 cm, median 9.5 cm, n = 10) than Common Kingfisher (3.8 to 5 cm, median 4.25 cm, n = 8), whereas the vertical diameter was almost same (Common: 7.7 to 10 cm, median 4.25 cm, n = 8; and White-throated: 7.5 to 12 cm, median 10.5 cm, n = 10). The average horizontal and vertical diameters of ovalshaped egg chamber of Common Kingfisher were, 11 to 15 cm, respectively (median 12.7 cm, n = 8) and 11 to 13 cm (median 11.6 cm, n = 8) and Whitethroated Kingfisher 11 to 21 cm (median 17 cm, n = 10) and 10 to 16 cm (median 12 cm, n = 10). Both species reused old nests through cleaning (37.5% in Common Kingfisher and 50% in White-throated Kingfisher) and the nest building periods were 12 to 20 days (16.1 ± 2.5 days, n = 8) and 8 to 18 days (13.2 ± 3.5 days, n = 10), respectively.Bangladesh J. Zool. 44(1): 99-109, 2016